Does Kinesiology Taping Improve Muscle Strength and Function in Knee Osteoarthritis? A Single-Blind, Randomized and Controlled Study - Halil ÖĞÜT; Hayal GÜLER; Mustafa Turgut YILDIZGÖREN; Onur VELİOĞLU and Ayşe Dicle TURHANOĞLU (Archives of Rheumatology, 2018)
Objectives: This study aims to evaluate the efficacy of kinesiology taping (KT) on pain, movement restriction, walking speed, daily living activities, and isokinetic muscle performance in female patients with knee osteoarthritis. Patients and methods: The study included 61 female patients (mean age 53.5±3.5 years; range 50 to 60 years) who were admitted to Physical Medicine and Rehabilitation Outpatient Clinic with complaints of mechanical knee pain. Knee osteoarthritis was diagnosed according to the clinical/ radiological criteria of the American College of Rheumatology and patients with Kellgren-Lawrence grade 2 and 3 were included. Patients were randomly divided into two groups. Both groups received transcutaneous electrical nerve stimulation for 30 minutes, hot pack for 30 minutes, and therapeutic ultrasound for 10 minutes in a day for three weeks (five days in a week). Also, one group was treated with KT (KT group, n=31) while the other group was treated with sham-KT (sham-KT group, n=30) one time a week for three weeks. A home program of around the knee strengthening exercises was recommended for all patients. All patients were evaluated with visual analog scale, Western Ontario and McMaster Osteoarthritis Index (WOMAC) values, goniometric measurement of active knee range of motion, 50-meter walking distance, and isokinetic knee extensor muscle peak torque measurements before treatment, at the end of treatment, and at one month and three months after treatment. Results: There was a significant improvement in after treatment and first month visual analog scale values in the KT group compared to the sham-KT group (p<0.05). In the KT group, the WOMAC pain and WOMAC total scores decreased significantly after treatment compared to the sham-KT group (p<0.05). Visual analog scale values were significantly decreased after treatment in both groups (p<0.05). In both groups; WOMAC pain, stiffness, physical function, and total values decreased significantly after treatment (p<0.05). In both groups, isokinetic quadriceps peak torque measurements were increased after treatment (p<0.05). Conclusion: The application of KT to females with knee osteoarthritis appears to be a method that may be effective on pain and functional capacity.